PENGARUH TENURE AUDIT DAN UMUR LISTING TERHADAP AUDIT REPORT LAG DENGAN SPESIALISASI INDUSTRI AUDITOR SEBAGAI MODERASI (Studi Empiris pada perusahaan LQ 45 yang terdaftar di Bursa Efek Indonesia Tahun 2011-2014) - Sabrina Octaviani; Enni Savitri; Supriono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to test the influence of tenure audit and listing age affect audit report lag with auditor industry specialization as a moderating variable of empirical studies on LQ 45 companies listed in Bursa Efek Indonesia during the period of 2011 – 2014. and tenure audit and listing afe are utilized as independent variables. Dependent variable in this research is audit report lag.Data used in this research are collected from financial statements of LQ 45 companies listed in IDX fact book and Indonesian Capital Market Directory. The population of this research comprise of LQ 45 companies listed in Bursa Efek Indonesia during the period of 2011 – 2014 with a total of 180 companies. The samples are determined using purposive sampling method. And the total samples of 76 companies. Data used in this research are secondary data from financial statement of the aforementioned manufacturing companies. Analysis of data is carried out using multiple regression method with the aid of SPSS Version 18 computer program.The result of this research before moderating show that tenure audit and listing age have significant on audit report lag. This research reveals that tenure audit and listing age moderated by auditor industry specialization shows shorter audit report lag compared to that of the non-specialists.Keywords: job insecurity, years of service, organizational commitment, pay satisfaction and turnover intentions